A survey of preparation for and experience of tourist health care among tourism organizations in 2019 - Nuchtean, Tuenjai; Damrongsak , Jariya; Chotanapan, Suthat (Journal of Medical and Public Health Region 4, 2022)
This study aims to survey of preparation for and experience of tourist health care among tourism organizations. Moreover, it focuses on finding recommendations and guidelines for monitoring travel health disease. This study was a descriptive design. It done by way of purposive sampling of 39 participants from guides and managers of tourism organizations to complete the questionnaire and examination test. The data were analyzed by using percentage, mean standard deviation (S.D.) and T-test. The results revealed that 71.79% of participants were female. The mean age of them all was 46.31 years old (S.D. = 12.34). Only 15.37% were older than 60 years old. Additionally, most of them worked more than 15 years (48.72%). The mean value of knowledge score before and after the training were 8.97 and 13.79, respectively. It indicated that participants had higher knowledge score after receiving training which considered statistically significant at p <0.05. About training experience, 56.41% took part in first aid, while 46.15% choose cardiopulmonary resuscitation. On the other hand, many of participants had never participated in travel health 76.92%. The findings on their healthcare experience proved that 35.90% of participants always give information or advice about healthcare to travelers before go abroad. When travelers had illness of accident during the trip. Participants could provide basic first aid, observe for sign and symptom, and order patient to take a rest. For severe cases, participants would contact hospitals or called ambulance. As for moderate cases, they would take that travellers to the nearest pharmacy or clinic. The recommendation from this study is public health organizations should have a role as mentor in order to support knowledge on travel health diseases (i.e., support training, provide health information brochures and guidelines). As well as, establishing a communication channel between tourism organizations and public health organizations. This way can help building a collaborative network on doing surveillance, prevention and control of travel health disease among travelers.